Renal Dysfunction after Living-Donor Liver Transplantation: Experience with 500 Cases - Ehab E. Abdel-Khalek; Alrefaey K. Alrefaey; Amr M. Yassen; Ahmed Monier; Hesham M. Elgouhari; Mohamed Samy Habl; Gehad Tawfik; Thuraya Elzayat; Reham Adly Zayed; Mohamed Abdel-Wahab (Journal of Transplantation)
Introduction. The possible risk factors for chronic kidney disease in transplant recipients have not been thoroughly investigated after living-donor liver transplantation. Material and Methods. A retrospective cohort study of consecutive adults who underwent living-donor liver transplantation between May 2004 and October 2016, in a single center, was conducted. Kidney function was investigated successively for all the patients throughout the study period, with 12 months being the shortest follow-up. Postoperative renal dysfunction was defined in accordance with the Chronic Kidney Disease Epidemiology Collaboration criteria. The patients’ demographic data, preoperative and intraoperative parameters, and outcomes were recorded. A calcineurin inhibitor-based immunosuppressive regimen, either tacrolimus or cyclosporine, was used in all the patients. Results. Of the 413 patients included in the study, 33 (8%) who survived for ≥1 year experienced chronic kidney disease 1 year after living-donor liver transplantation. Twenty-seven variables were studied to compare between the patients with normal kidney functions and those who developed chronic kidney disease 1 year after living-donor liver transplantation. Univariate regression analysis for predicting the likelihood of chronic kidney disease at 1 year revealed that the following 4 variables were significant: operative time, P < 0.0005; intraoperative blood loss, P < 0.0005; preoperative renal impairment, P = 0.001; and graft-to-recipient weight ratio (as a negative predictor), P < 0.0005. In the multivariate regression analysis, only 2 variables remained as independent predictors of chronic kidney disease at 1 year, namely, operative time with a cutoff value of ≥714 minutes and graft-to-recipient weight ratio as a negative predictor with a cutoff value of <0.91. Conclusion. In this study, prolonged operative time and small graft-to-recipient weight ratio were independent predictors of chronic kidney disease at 1 year after living-donor liver transplantation.